A brief Account of Geography Teaching at Prithvi Narayan Campus, Pokhara - KC, Krishna (The Himalayan Geographers, 2025)
This article provides a brief yet comprehensive account of the development of geography teaching at Prithvi Narayan Campus, Pokhara, since its initiation in 1962. It explores the historical background of the Department of Geography, its foundation, and gradual evolution in the context of higher education expansion in western Nepal. The methods of the study is based on qualitative analysis of institutional records, archival documents, internal publications, and relevant literature. Both primary and secondary data sources were utilized, particularly campus and departmental archives. The study aims to document significant milestones in the department’s journey, identify and acknowledge the contributions of both national and international faculty members, and highlight the department's academic progress, including its infrastructure, research activities, and curricular expansion. Notable developments include the introduction of Bachelor's and Master's programs, incorporation of population studies, and the establishment of a GIS and Remote Sensing laboratory with international collaboration. The department has also made notable contributions to applied research, academic seminars, and training programs over the decades.